the Pengembangan Media Pembelajaran Seragam Sekolah Negosiasi pada Materi Teks Negosiasi Siswa Kelas X SMA Negeri 1 Lingga Utara Tahun Pelajaran 2022/2023 - Melan; Legi Elfitra; Harry Andheska (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Learning media can help teachers and students in the learning process in the classroom. This research is development research which aims to produce visual media. This research uses the PPE development model proposed by Rickey and Klein. The test subjects in this research were class The data collection techniques in this research consist of 2, namely validity (by media experts and material experts) and practicality (by small groups, large groups and Indonesian language teachers). The results of this research show that the assessment from media experts was 95%, material experts were 86%, small groups were 93.5%, large groups were 95.5% and Indonesian language teachers were 94%.